Long Non-Coding RNAs in Gliomas: From Molecular Pathology to Diagnostic Biomarkers and Therapeutic Targets - Vecera, Marek; Sana, Jiri; Lipina, Radim; Smrcka, Martin; Slaby, Ondrej (International journal of molecular sciences, 2018)
Gliomas are the most common malignancies of the central nervous system. Because of tumor localization and the biological behavior of tumor cells, gliomas are characterized by very poor prognosis. Despite significant efforts that have gone into glioma research in recent years, the therapeutic efficacy of available treatment options is still limited, and only a few clinically usable diagnostic biomarkers are available. More and more studies suggest non-coding RNAs to be promising diagnostic biomarkers and therapeutic targets in many cancers, including gliomas. One of the largest groups of these molecules is long non-coding RNAs (lncRNAs). LncRNAs show promising potential because of their unique tissue expression patterns and regulatory functions in cancer cells. Understanding the role of lncRNAs in gliomas may lead to discovery of the novel molecular mechanisms behind glioma biological features. It may also enable development of new solutions to overcome the greatest obstacles in therapy of glioma patients. In this review, we summarize the current knowledge about lncRNAs and their involvement in the molecular pathology of gliomas. A conclusion follows that these RNAs show great potential to serve as powerful diagnostic, prognostic, and predictive biomarkers as well as therapeutic targets.
Keywords: gliom; diagnosis; prognóza; biomarker; RNA dlouhá nekódující; long non-coding RNA; glioblastoma; molekulární patologie; molecular pathology; RNA, Long Noncoding; Glioma; prognosis; Animals; lidé; Humans; zvířata; glioma; Pathology, Molecular; Prognosis; Biomarkers, Tumor; nádorové biomarkery